A user’s guide to data from Round 1.5 of the Pakistan Rural Household Panel Survey (PRHPS) 2012 - International Food Policy Research Institute; Innovative Development Strategies (International Food Policy Research Institute, 2014)
Pakistan Rural Household Panel Survey 2012 (Round 1.5), a sub-sample consisting of agricultural households captured in Round 1 of the Panel Survey, gathers detailed information on agricultural production and related issues from rural households in Pakistan. Round 1.5 covers 942 agricultural households in 76 primary sampling units in the rural areas of three provinces namely: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK). This survey covers information of households, who either managed or cultivated agricultural plots, during the production year 2011-12, and two crop seasons, namely: (i) Kharif 2011; (ii) Rabi 2011-12. It gathers information on agricultural production (including inputs and outputs or crop and livestock production), agricultural water use, farm and household assets, access to extension services, climate change, credit, employment and income, household consumption and expenditures, and the linkage between pesticides and health. The sample is nationally representative of the rural areas of the three provinces. Data was collected at household, individual and crop level using a household level questionnaire.